Patterns of axillary staging and management in clinically node positive breast cancer patients treated with neoadjuvant systemic therapy: Results of a survey amongst breast cancer specialists. Issue 1 (January 2020) - Simons, J.M.; Maaskant-Braat, A.J.G.; Luiten, E.J.T.; Leidenius, M.H.K.; van Nijnatten, T.J.A.; Boelens, P.G.; Koppert, L.B.; van der Pol, C.C.; van de Velde, C.J.H.; Audisio, R.A.; Smidt, M.L.
Abstract: Introduction: Various options for axillary staging after neoadjuvant systemic therapy (NST) are available for breast cancer patients with a clinically positive axillary node (cN+). This survey assessed current practices amongst breast cancer specialists. Materials and methods: A survey was performed amongst members of the European Society of Surgical Oncology and two UK-based Associations: the Association of Breast Surgery and the British Association of Surgical Oncology. The survey included 3 parts: 1. general information, 2. diagnostic work-up and 3. axillary staging after NST. Results: A total of 310 responses were collected: parts 1, 2 and 3 were fully completed by 282 (91%), 270 (87.1%) and 225 (72.6%) respondents respectively. After NST, 153/267 (57.3%) respondents currently perform ALND routinely and 114 (42.7%) respondents perform less invasive restaging of the axilla with possible omission of ALND. In the latter group, 85% does and 15% does not use nodal response seen on imaging to guide the axillary restaging procedure. Regarding respondents that do use imaging: 95% would perform a less invasive staging procedure in case of complete nodal response on imaging (63% sentinel lymph node biopsy (SLNB), excision of a previously marked positive node with SLNB (21%) and without SLNB (11%)). In case of no nodal response on imaging 77% would perform ALND. Conclusion: Current axillary staging and management practices in cN + patients after NST vary widely. To determine optimal axillary staging and management in terms of quality of life and oncologic safety, breast specialists are encouraged to include patients in clinical trials/prospective registries.